Predictability of postural sway: unraveling the impact of simulated somatosensory deficits using a rambling-trembling approach - Gerber, Eryn D.; Huang, Chun-Kai; Giraldo, Camilo; Nichols, Paris; Luchies, Carl W. (Frontiers in Bioengineering and Biotechnology, 2025)
One of the primary contributors to falls in older adults is somatosensory degeneration. A method of center-of-pressure (COP) analysis, rambling-trembling (RM-TR) decomposition, has the potential to significantly improve balance deficit detection. However, its ability to capture sensation-driven changes to postural sway is not well understood. Therefore, the objective of this study is to quantify the effects of progressive simulated somatosensory deficit on COP, RM and TR time series. Fifty-one healthy adults (aged 22.10 ± 1.88 years) completed three 60-s double-limb, quiet standing trials with eyes closed for each randomly-ordered foam thickness condition (no foam, 1/8″, 1/4″, 1/2″, and 1″). Foot-floor kinetic data was collected at 100 Hz using two 6-axis force plates and a 16-bit A/D acquisition system. The data were filtered with a 2nd-order 10 Hz low-pass Butterworth filter and used to calculate COP, RM and TR time series. Range, root-mean-square (RMS), and sample entropy (SampEn) were calculated for each time series. Repeated measures analyses of variance, with α = 0.05, were conducted to compare foam condition for each measure (range, RMS, and SampEn). Results showed range and RMS increased with foam thickness; thicker foams (F3–F4) produced larger increases than thinner foams (F1–F2), with more prominent effects in the AP than ML direction. SampEn decreased as foam thickness increased, but not for all comparisons or measures. TR consistently showed the greatest SampEn values compared with COP and RM. Our findings suggest that RM-TR decomposition can isolate distinct biomechanical contributions to postural sway, each influenced independently by somatosensation. Future work should continue to explore the utility of RM-TR decomposition, particularly in aging populations, to advance our understanding of sensory contributions to postural control and assess its viability as a clinical assessment tool.